Mid-term results of intralesional extended curettage, cauterization, and polymethylmethacrylate cementation in the treatment of giant cell tumor of bone: A retrospective case series - AKGÜLLE, AHMET HAMDİ; EROL, BÜLENT; ŞİRİN, EVRİM; TOPKAR, OSMAN MERT; BAYKAN, SAİD ERKAM (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2020)
Objective: The aim of this study was to present the mid-term functional outcomes and recurrence rate in patients with giant cell tumor of bone (GCTB) treated by intralesional extended curettage, electrocauterization, and polymethylmethacrylate (PMMA) cementation. Methods: In this retrospective observational study, 79 consecutive patients (41 females, 38 males; mean age=39 years; age range=19-62 years) who were diagnosed and treated for GCTB between 2005 and 2017 were identified from hospital medical records. All patients were treated by intralesional extended curettage using high-speed burr, electrocauterization of the cavity, and filling the defect with PMMA. No additional local adjuvants were used. The mean follow-up period was 47 months (range=24-96). The tumors were graded according to the radiological classification system described by Campanacci. Functional outcomes were evaluated using the Musculoskeletal Tumor Society Score (MSTS) preoperatively, one year postoperatively, and at the final follow-up. Postoperative complications and recurrence rates were recorded. Results: Twenty-nine tumors were located in the distal femur, 23 in the proximal tibia, nine in the distal radius, five in the proximal humerus, five in the pelvis, three in the proximal fibula, two in the distal ulna, two in the distal tibia, and one in the second metatarsal. According to Campanacci classification, 37 tumors were grade III, 32 grade II, and 10 grade I. The mean MSTS score was 46.1% (range 40.2 to 71.4%) preoperatively, 91.7% (range 73.3% to 100%) one year postoperatively, and 86.3 % (range 66.2% to 96,1%) at the final follow-up. The overall complication rate was 7.6%; which included local tumor recurrence in four patients, superficial wound infection in one, and deep wound infection in another. The recurrence rate was 5.1% (4 patients). Recurrent tumors were located at the distal femur in three patients and proximal tibia in one. Conclusion: With satisfactory functional results and low recurrence rates at the mid-term follow-up, GCTB can be treated effectively with intralesional extended curettage, electrocauterization, and PMMA cementation.
Keywords: Giant cell tumor of bone; Curettage; Polymethylmetacrylate; Recurrence; Local adjuvant; SOFT-TISSUE EXTENSION; LOCAL RECURRENCE; LONG BONES; PHENOL; ADJUVANTS